THE SCIENTIFIC SIGNIFICANCE OF THE HARMONY OF THE WORKS OF ABU ALI IBN SINA AND ALISHER NAVAI - Akhatova Dildora Akhtamovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article compares some of the works of poetry and prose of Abu Ali ibn Sina, who is one of the thinkers of the East, and Alisher Navoi, sultan of the Gazelle dynasty. Among them "At-Tayr" - "Bird Business", "Big Collection on Musical Science", "Lison ut-Tair" by Alisher Navoi. Both Ibn Sina and Alisher Navoi based their work on the issue of man, and it should be noted that these works are important in the spiritual development of man.